Kenaf-filled thermoplastic polyurethane-natural rubber composite for automotive engine rubber mount - Abdul Murat, Noor Azammi (2019)
This study focuses on the compatibility of natural rubber (NR) and thermoplastic polyurethane (TPU) blends with kenaf fiber as filler. The early stage is to prepare the raw material as the NR is in liquid form, while the TPU is in resin form. All three material is then blended into the Brabender machine using the correct temperature. When the three material is bonded nicely, is then prepared into sample board using 40-tonne hot press machine using specific temperature and cut into specific specimen sample according to the ASTM standard required. The first aim is to identify the mechanical properties of the new develop composite such as tensile, flexural, impact, thermal and kinetic behaviour. The physical test is then compared to the untreated and the treated kenaf using NaOH. The comparison is done to identify the bonding effect between the polymer composite. The result for tensile strength achieve for untreated and treated is almost the same which is 5.5 Mpa. The flexural strength for the untreated fiber is 4 Mpa and for the treated fiber is 3.4 MPa. Meanwhile for the impact strength for the treated fiber shows slightly higher 2.5 MPa then the untreated fiber which is 1 MPa. The bonding comparison is carefully observe using a scanning electron microscope (SEM). The TPU-NR kenaf filler polymer composite the then proposed to be applied in the automotive parts such as engine rubber mounting to replicate the standard engine rubber mountings function. A conceptual design study has been initiated to select the new conceptual engine rubber mounting design using TRIZ, morphology chart and analytical network programme (ANP). Finally, the selected engine mounting design will be analysed using ANSYS simulation for stress-strain analysis to check the compatibility of the TPU-NR kenaf filled polymer composite with the engine mounting design. A simple stress and deformation simulation using ANSYS are conducted towards the final product design. The performance of rubber mounting is tested with several loading conditions to studies the capabilities of the engine mounting using ANSYS simulation.